Edukasi Kesehatan Reproduksi melalui Webinar “Hormone Talk” sebagai Upaya Peningkatan Pengetahuan tentang Menstruasi, PCOS, dan Deteksi Dini pada Perempuan Usia Produktif - Zahwalia Putri; Suci Rahayu; Aulia Chintya Sari (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2026)
Reproductive health is an aspect of health that still requires serious attention, particularly for women of reproductive age. Polycystic Ovary Syndrome (PCOS) is a hormonal disorder with a prevalence of 3.4% among women worldwide, yet it often goes undetected due to a lack of awareness. This community service activity aims to increase the knowledge of women of reproductive age regarding menstruation, PCOS, and the importance of early detection through an educational webinar titled “Hormone Talk: Exploring Menstruation, PCOS, and the Importance of Early Detection.” The event was held online via the Zoom Meeting platform on December 13, 2025, and was attended by over 100 participants, the majority of whom were female students. The evaluation method utilized pre-tests and post-tests analyzed using a Dependent T-test. The results showed a significant increase in the average knowledge score from 64.78 (pre-test) to 79.67 (post-test), with a difference of 14.89 points and a p-value of 0.000. This demonstrates that reproductive health educational webinars are effective in enhancing participants’ knowledge. It is hoped that this activity can serve as a model for sustainable digital-based health promotion interventions in efforts to improve reproductive health literacy among Indonesian women.